2016
DOI: 10.1097/md.0000000000003572
|View full text |Cite|
|
Sign up to set email alerts
|

Medication Adherence and Blood Pressure Control Among Hypertensive Patients With Coexisting Long-Term Conditions in Primary Care Settings

Abstract: Hypertension is a typical example of long-term disease posing formidable challenges to health care. One goal of antihypertensive therapy is to achieve optimal blood pressure (BP) control and reduce co-occurring chronic conditions (multimorbidity). This study aimed to assess the influence of multimorbidity on medication adherence, and to explore the association between poor BP control and multimorbidity, with implications for hypertension management.A cross-sectional design with multistage sampling was adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 53 publications
7
34
2
2
Order By: Relevance
“…In the present study, the patients with controlled BP were older on average, and higher percentages had comorbidities such as heart disease, left ventricular hypertrophy, and kidney disease. This is partly in contrast with other studies, which have found older age and the presence of left ventricular hypertrophy and multimorbidity to be predictive of a lack of BP control . However, coronary heart disease has previously been associated with a greater chance of achieving BP control .…”
Section: Discussioncontrasting
confidence: 93%
“…In the present study, the patients with controlled BP were older on average, and higher percentages had comorbidities such as heart disease, left ventricular hypertrophy, and kidney disease. This is partly in contrast with other studies, which have found older age and the presence of left ventricular hypertrophy and multimorbidity to be predictive of a lack of BP control . However, coronary heart disease has previously been associated with a greater chance of achieving BP control .…”
Section: Discussioncontrasting
confidence: 93%
“…However, recent investigations indicate that some self-reported data have a significant overlap with medical data for the most prevalent chronic diseases found in our study, such as diabetes, hypertension and hypercholesterolemia [87,88,89]. Future studies should also include other possible determinants of multimorbidity such as drug adherence, and utilization of health services as recently reported in primary care settings [90]. …”
Section: Discussionmentioning
confidence: 62%
“…From the literature review, it was evident that the majority of publications were about countries with a developed HTA structure, such as Argentina, Brazil, Canada, Chile, Colombia, and Mexico (2,4,7,8,10,13,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). This shortage of information reinforces the need for research in countries with less developed HTA and decision-making processes.…”
Section: Discussionmentioning
confidence: 99%